Poverty in Malawi, 2016–2017 - International Food Policy Research Institute (International Food Policy Research Institute, 2019)
This poster complements our fifth Key Facts Sheet on poverty in Malawi, published in May 2019. The maps and the table are based on data from the fourth Integrated Household Survey (IHS4), which were collected in 2016-2017.